2013
DOI: 10.1002/elps.201300354
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule study of DNA collision with elliptical nanoposts conveyed by hydrodynamics

Abstract: Periodic arrays of micro-or nano-pillars constitute solid state matrices with excellent properties for DNA size separation. Nanofabrication technologies offer many solutions to tailor the geometry of obstacle arrays, yet most studies have been conducted with cylinders arranged in hexagonal lattices. In this report, we investigate the dynamics of single DNA collision with elliptical nanoposts using hydrodynamic actuation.Our data shows that the asymmetry of the obstacles has minor effect on unhooking dynamics, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Previously, a post array has been utilized to separate large DNA molecules based on their lengthdependent hooking and unhooking dynamics under the external electric field. [5][6][7][8][9][10][11] In addition, it was proposed that a nanopost array can template the self-assembly of block copolymers to form specific patterns. [12][13][14] Recent advances in the nano-fabrication may find more versatile uses of the nanopost system, thanks to the ability to prepare an array of nanoposts with a wide range of dimensions and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a post array has been utilized to separate large DNA molecules based on their lengthdependent hooking and unhooking dynamics under the external electric field. [5][6][7][8][9][10][11] In addition, it was proposed that a nanopost array can template the self-assembly of block copolymers to form specific patterns. [12][13][14] Recent advances in the nano-fabrication may find more versatile uses of the nanopost system, thanks to the ability to prepare an array of nanoposts with a wide range of dimensions and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3(d) shows an example: the instantaneous polyelectrolyte CM velocity is minimum at the inflection point t = tI of the xe(t) vs t curve; this defines the velocity vI-see Eq. (8). The trajectory of the uncharged polymer [Fig.…”
Section: B Anatomy Of a Collisionmentioning
confidence: 99%
“…5 Surprisingly, Barron et al 6 showed in a seminal 1994 paper that ultra-dilute polymer solutions can be used in capillary electrophoresis to separate large DNA molecules, forcing us to revisit the concept of sieving. 7 Polymer collisions have thus been extensively studied; examples include DNA molecules colliding with cylindrical poles, [2][3][4] gel fibers, 5 various types of obstacles, 8,9 and uncharged polymers. 10 Excellent review articles have covered this field.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, single-spot LAMP with signal enhancement achieved the rapid detection of virus DNA [ 9 ]. However, fluctuations of the reaction are a serious concern in single-spot reactions, which might come from the molecular transportation and collision frequency problem [ 31 ]. Hence, a new strategy of using a nanoarray for parallel FRET-LAMP was conducted to overcome this problem.…”
Section: Introductionmentioning
confidence: 99%